Developing Pre-Service Mathematics Teachers’ TPACK through Digital Learning Environments: A Literature Review - Agusalim Juhari; Abdurahman Hamid (International journal of technology and education research, 2026)
The development of pre-service mathematics teachers’ competence in integrating technology has become a central issue in contemporary teacher education. One of the most widely used frameworks for understanding this competence is Technological Pedagogical Content Knowledge (TPACK), which refers to the integrated knowledge of technology, pedagogy, and subject matter. This article aims to review how digital learning environments contribute to the development of pre-service mathematics teachers’ TPACK. Using a narrative literature review approach, this article synthesizes studies published between 2010 and 2025 that discuss TPACK, mathematics teacher education, digital learning environments, dynamic mathematics software, virtual simulations, technology-based microteaching, collaborative task design, online and hybrid learning, and professional development. The review indicates that digital learning environments can strengthen TPACK when technology is not treated merely as a technical tool, but is embedded in pedagogical design and mathematical representation. TPACK development is more effective when pre-service teachers engage in authentic learning experiences, such as technology-based task design, digital microteaching, virtual simulation, collaborative lesson planning, feedback, reflection, and the use of dynamic mathematics software. However, several challenges remain, including infrastructure limitations, unequal access to digital tools, variation in digital literacy, limited institutional support, and the lack of longitudinal evidence on the sustainability of TPACK development in real teaching practice. This article argues that mathematics teacher education programs need to design digital learning environments that are structured, contextual, reflective, collaborative, and sustainable so that TPACK development moves beyond technical proficiency toward meaningful pedagogical competence.